Trends in gabapentinoid prescribing, co-prescribing of opioids and benzodiazepines, and associated deaths in Scotland. (August 2020) - Torrance, Nicola; Veluchamy, Abirami; Zhou, Yiling; Fletcher, Emma H.; Moir, Eilidh; Hebert, Harry L.; Donnan, Peter T.; Watson, Jennifer; Colvin, Lesley A.; Smith, Blair H.
Abstract: Background: Gabapentinoid drugs (gabapentin and pregabalin) are effective in neuropathic pain, which has a prevalence of ∼7%. Concerns about increased prescribing have implications for patient safety, misuse, and diversion. Drug-related deaths (DRDs) have increased and toxicology often implicates gabapentinoids. We studied national and regional prescribing rates (2006–2016) and identified associated sociodemographic factors, co-prescriptions and mortality, including DRDs. Methods: National data from the Information Service Division, NHS Scotland were analysed for prescribing, sociodemographic, and mortality data from the Health Informatics Centre, University of Dundee. DRDs in which gabapentinoids were implicated were identified from National Records of Scotland and Tayside Drug Death Databases. Results: From 2006 to 2016, the number of gabapentin prescriptions in Scotland increased 4-fold (164 630 to 694 293), and pregabalin 16-fold (27 094 to 435 490). In 2016 'recurrent users' (three or more prescriptions) had mean age 58.1 yr, were mostly females (62.5%), and were more likely to live in deprived areas. Of these, 60% were co-prescribed an opioid, benzodiazepine, or both (opioid 49.9%, benzodiazepine 26.8%, both 17.1%). The age-standardised death rate in those prescribed gabapentinoids was double that in the Scottish population (relative risk 2.16, 95% confidence interval 2.08–2.25). Increases in gabapentinoids contributing to cause of DRDs were reported regionally and nationally (gabapentin 23% vs 15%; pregabalin 21% vs 7%). In Tayside, gabapentinoids were implicated in 22 (39%) of DRDs, 17 (77%) of whom had not received a prescription. Conclusions: Gabapentinoid prescribing has increased dramatically since 2006, as have dangerous co-prescribing and death (including DRDs). Older people, women, and those living in deprived areas were particularly likely to receive prescriptions. Their contribution to DRDs may be more related to illegal use with diversion of prescribed medication.